ANALISIS PENGARUH PENAMBAHAN ABU AMPAS TEBU SEBAGAI FILLER TERHADAP KARAKTERISTIK MARSHALL PADA ASPAL AC-WC - Rosyad, Farlin; Putri, Della (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Asphalt is a thick liquid which is a hydrocarbon compound with small amounts of sulfur, oxygen and chlorine. Asphalt as a binding material for flexible pavement has viscoelastic properties, a combination of elastic and viscous properties. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, sugarcane bagasse ash, which is easily obtained, was used in research as an alternative in asphalt mixtures. Based on the Marshall test results, the highest density value variation in terms of density is at a percentage of 3%, amounting to 2.239gr. The stability value is at a percentage of 3% of 1464gr. The flow value is at a percentage of 0.5% of 4. The VIM value is at a normal percentage of 5.04. The VMA value is at a percentage of 0.5% of 16.99. The VFA value is at the 3% percentage of 61.09. The MQ value is in the normal percentage of 517. The Residual Marshall Stability Value is in the 3% percentage of 91.43.Keywords: Bagasse Ash, Asphalt, Marshall